Kedudukan hormon tumbesaran di kalangan pesakit talasemia - Rasid, Mazidah Abdul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Aim: The aim of this study is to compare the pattern of growth hormone secretion and serum IGF-1 in children with transfusiop dependent thalassemia and normal children. Method: Children aged 6-12 years with transfusion dependent thalassemia were randomly selected from children with thalassemia admitted to University of Science Malaysia Hospital from October 1993 to October 1995. None of the patients gave a family history of malnutrition, diabetes mellitus, dwarfism or other endocrine diseases. Normal children volunteers were mainly healthy children of staff members in the hospital. The heights, bone age, serum ferritin and serum IGF-1 were measured in all the children. Serum growth hormone was measured following stimulation with exercise and intravenous glucagon. Both serum growth hormone and serum IGF-1 were estimated by radioimmunoassay using a double antibody. Results: A total of 22 thalassemic children (4 P-thalassemia major and 18 HbEIP-thalassemia) and 10 normal children were studied. There was no difference in sex, mean chronological age and mean bone age between thalassemic and..flprmal children. The Z-scores and serum ferritin were significantly more in thalassemic than normal children. The serum thyroxine and thyroid stimulating hormone were normal in both groups. The mean peak serum growth hormone following exercise and intravenous glucagon was 4.2 ug/L and 3.8 ug!L in thalassemic children and 3.6 ug/L and 4.8 ug/L in normal children respectively. There were not statistically significant. The mean serum IGF-1 levels was significantly higher (p = 0.001) in the normal (25.5 ng/L) than the thalassemia children (12.3 ng/L). In thalassemia children there was no correlation between serum ferritin and .age (r =- 0.04) and between serum ferritin level and serum IGF-1 levels (r = 0.01). There was only a weak negative correlation between serum ferritin and peak growth hormone levels after exercise (r = - 0.30) and glucagon stimulation (r = - 0.29). Conclusion: GH secretion, as evaluated by the responses to exercise and glucagon stimulation, is not impaired, while the generation of serum IGF-1 is reduced in this group of thalassemic children. Comparison of these data with those of other published reports indicate that impairment of GH secretion may occur later in the course of the disease. A reduction in IGF-1 production probably secondary to excessive iron deposition in the liver is manifested earlier. The presence of impaired IGF-1 production may be a cause of short stature in these children. The achievement of relatively constant haemoglobin levels and reduction of tissue iron stores with long term iron chelation therapy is needed to prevent these endocrine abnormalities.